ANALISIS EKSTERNALITAS INDUSTRI PENGGILINGAN PADI DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Suhada, Fadel Fathi; Prasmatiwi, Fembriarti Erry; Firdasari, Firdasari (Lampung University, 2024)
This study aims to analyze the profit of rice milling industry by including and excluding the externalities costs and analyze the externalities of the rice milling industry to the community in Gadingrejo Sub-district, Pringsewu Regency. The analytical methods used were profit analysis and descriptive quantitative by analyzing social, economic, and environmental aspects to analyze externalities to the community. This study was conducted in two different scale of mills, namely mill B (big scale) and mill K (small scale). The number of respondents was 30 peoples from communities surrounding each mill. Data collection was conducted from October to December 2023. The results show that by excluding the externalities costs, the profit earned by milling B is 9.867.908.333,00/year and a profit earned by including externalities costs is Rp9.724.308.333,00/year. Meanwhile, the profit earned by milling K without externalities costs is Rp770.205.750,00/year and the profit earned by including externalities costs is Rp766.005.750,00/year. The positive externalities of milling B include active social activities, providing assistance, maintaining friendship, providing rice, creating new business opportunities, increasing job opportunities, facilitating grain marketing, building village facilities and infrastructure, making efforts to protect the environment, and sustain the environment. The positive externalities of milling K are similar to milling B. Meanwhile, the negative externalities caused by milling K include dust that polluted the environment and loud noise that disturbing the neighbourhood, while milling B does not cause any negative externalities that disturb the community. Keywords: externalities, pollution, profit, rice milling, waste